21 Speeches that Shaped our World : The People and Ideas that Changed the way we Think - Abbott, Chris (London Rider, 2012)
In this fascinating book, Chris Abbott, a leading political analyst, takes a close look at 21 key speeches which have shaped the world today.
Include Illustrations and Index
Keywords: Speeches, addresses, etc -- History, Modern